Transcriptome Analysis of the Cf-12-Mediated Resistance Response to Cladosporium fulvum in Tomato - Xue, Dong-Qi; Chen, Xiu-Ling; Zhang, Hong; Chai, Xin-Feng; Jiang, Jing-Bin; Xu, Xiang-Yang; Li, Jing-Fu (Frontiers in Plant Science, 2017)
Cf-12 is an effective gene for resisting tomato leaf mold disease caused by Cladosporium fulvum (C. fulvum). Unlike many other Cf genes such as Cf-2, Cf-4, Cf-5 and Cf-9, no physiological races of C. fulvum that are virulent to Cf-12 carrying plant lines have been identified. In order to better understand the molecular mechanism of Cf-12 gene resistance response, RNA-Seq was used to analyze the transcriptome changes at three different stages of C. fulvum infection (0, 4 and 8 days post infection [dpi]). A total of 9,100 differentially expressed genes (DEGs) between 4 and 0 dpi, 8,643 DEGs between 8 and 0 dpi and 2,547 DEGs between 8 and 4 dpi were identified. In addition, we found that 736 DEGs shared among the above three groups, suggesting the presence of a common core of DEGs in response to C. fulvum infection. These DEGs were significantly enriched in defense-signaling pathways such as the calcium dependent protein kinases pathway and the jasmonic acid signaling pathway. Additionally, we found that many transcription factor genes were among the DEGs, indicating that transcription factors play an important role in C. fulvum defense response. Our study provides new insight on the molecular mechanism of Cf resistance to C. fulvum, especially the unique features of Cf-12 in responding to C. fulvum infection.